Research Progress of Bubble Pump in Refrigeration Application - Liang Yu; Liu Daoping; Ye Peng (Zhileng xuebao)
A literature review on bubble pump using in refrigeration technology and a brief introduction the principle of bubble pump are provided. A number of bubble pumps that apply to diffusion-absorption refrigeration, Einstein refrigeration cycle, absorption refrigeration and solar refrigeration are provided and discussed. Configuration, operating parameter and working fluid are presented as the important parameters influencing the performance of the bubble pump. Finally, the fundamental theory of bubble pump, working characteristics and the performance of bubble pump improvement are proposed to be researched preferentially.